Concepts, explanation theories, standards and guidelines on corporate social responsibility: Overview of research and contact with Vietnam - HANG, BUI THI THU (The journal of contemporary issues in business and government, 2021)
In a developing country like Vietnam, businesses are, in many different ways, making an effort to integrate into the international business community. To achieve this purpose, one of the main strategies is to carry out CSR. Based on content analysis and statistical methods, the study systematically reviewed the existing literature indexed in Google Scholar, Google, and the library. The research’s primary goal is to provide a theoretical basis for scholars, especially Vietnamese ones, to reasonably design CSR measurement indicators for future quantitative research. As a result, the paper presented CSR concepts that stand out from each historical period, moreover, placed in connection with theories explaining whether incorporations should engage in CSR activities or not. Besides, the paper introduces a range of international CSR standards and guidelines, with an emphasis on GRI and ISO26000. From the perspective of Vietnam, this country’s government also applied ISO 26000 to develop its national standards on CSR. Vietnamese enterprises can also consult GRI to implement CSR activities as well as prepare sustainability reports. They must comply with legal provisions on CSR information disclosure and refer to Vietnamese guidelines such as the Corporate Governance Principles, the Corporate Sustainable Index 2020.